Integration of Multimedia Development Life Cycle (MDLC) and User-Centered Design (UCD) Methods in the Development of Vegetable Variety Recognition Puzzle Game for Children - Renna Yanwastika Ariyana; Prita Haryani; Fx. Guntur Putra Susanto; Nizar Izzuddin Yatim Fadlan (Universitas Islam Raden Rahmat, Malang, 2025)
Introducing the content and benefits of Vegetables to children is one way to increase understanding of the importance of a balanced diet and its relationship with health. Vegetables are a source of nutrients for the body, especially for optimal growth and development of children. Introducing various types of Vegetables through visualized media by utilizing a touch of technology is one of the best ways to introduce the benefitss of Vegetables to children. In the research conducted, the Multimedia Devlopment Life Cycle (MDLC) method and the User Centred Design (UCD) method will be integrated in the development of a puzzle game to introduce various Vegetables to children. The final result of the research conducted is a puzzle game application used to introduce a variety of Vegetables to children, by integrating the MDLC method for the development stages and UCD for UI / UX development tailored to user needs.